IoT smart energy monitoring system - Tay, Yong Tang (2023)

(untitled)
Indoor plantation is popular among every household to keep people enjoying living in a green space, keep their house fresh, and most like having gorgeous plants around. However, people nowadays have hectic schedules. It is difficult for them to pay more attention to their plants at home while they are working. In this project, an IoT smart agriculture and smart irrigation system is developed. This system is able to measure air temperature and air humidity by using the DHT22 sensor; soil moisture in two different areas by using two capacitive soil moisture sensors; and the water level in the water tank by using an ultrasonic sensor. The Node MCU ESP32 DEVKIT V1 DOIT development board is used in this project to interface with the Blynk server. The conditions of the plants are sent to the cloud and displayed on the smartphone via the Blynk IoT application. Besides that, the conditions can also be displayed physically by using the OLED display. Then, this system includes a smart irrigation system that is operated with the stepper motor, the water pump, and the automations that can be activated in the Blynk IoT app. When the soil moisture is fall below 30 %, a notification is sent to the smartphone, and the irrigation system is activated. In addition, another automation is applied to detect the water level of the water tank and send a notification when the water level is below 15 %. After that, the reliability of this system is analysed, and the overall performance of the display system, irrigation system, and automation achieved above 90 % accuracy. The energy saving efficiency analysis shows that the smart irrigation system is able to save 80.65 % of water when the plants are placed in a cold environment and 67.74 % of water when the plants are placed in a room temperature environment. Lastly, the improvement of this project is suggested by implementing the camera and artificial intelligence in this system.